Pemanfaatan Media Sosial pada Pengembangan UMKM Desa Wisata Kepuh, Kabupaten Cirebon - Farida Hariyati; Abdul Khohar; Muhammad Azidan (Jurnal Media Pengabdian Komunikasi, 2022)
Abstract Cirebon is one of the cities in West Java Province which has potential and is a local and culinary tourism destination that is widely known to the public. In addition to the tourist icons that have surfaced, several villages in Cirebon also have tourism potential, such as in Kepuh Village, Palimanan District. Kepuh Village has tourist destinations such as Raden Benadi Park which has the potential to become a local tourist spot, in addition to food products from MSMEs such as rangginan, banana chips, and various processed cassava. The potential for tourism through the development of rural MSMEs can be well recognized by the public if the management is carried out creatively and utilizes social media. The media is able to build images, display visuals, audio and informative messages, entertain and invite audience curiosity with well-managed posts. Regarding the development of tourist villages through the use of social media, lecturers and students of the UHAMKA Communication Studies Study Program conducted outreach and training as part of the Collaborative Student Work Lecture Program (KKM) coordinated by the Muhammadiyah University of Cirebon (UMC) with Muhammadiyah universities in Central Java, Java. Barat, and DKI Jakarta will implement the Merdeka Campus Program for Tourism Villages in achieving the Sustainable Development Goals (SDGs). This activity provides benefits for MSME actors in Kepuh Village by gaining skills in creating social media accounts, practicing making photo posts with interesting angles, as well as captions that can invite readers so they are interested in exploring further.Key words: Branding; tourist villages; social media; UMKM. Â Â AbstrakCirebon merupakan salah satu kota di Provinsi Jawa Barat yang memiliki potensi dan menjadi salah satu tujuan wisata lokal dan kuliner yang banyak dikenal masyarakat. Di samping ikon-ikon wisata yang telah mengemuka, beberapa desa di Cirebon juga memiliki potensi wisata seperti di Desa Kepuh, Kecamatan Palimanan. Desa Kepuh memiliki destinasi wisata seperti Taman Raden Benadi yang berpotensi menjadi tempat wisata lokal, disamping produk makanan dari UMKM seperti rangginan, keripik pisang, dan aneka olahan singkong. Potensi pariwisata melalui pengembangan UMKM desa dapat dikenal dengan baik oleh khalayak jika pengelolaannya dilakukan secara kreatif dan memanfaatkan media sosial. Media mampu membangun citra, menampilkan visual, audio, dan pesan-pesan informatif, menghibur, dan mengundang rasa ingin tahu khalayak dengan postingan yang dikelola dengan baik. Berkaitan dengan pengembangan desa wisata melalui pemanfaatan media sosial, dosen dan mahasiswa Prodi Ilmu Komunikasi UHAMKA melakukan sosialisasi dan pelatihan sebagai bagian dari Program Kuliah Kerja Mahasiswa (KKM) Kolaboratif yang dikoordinatori oleh Universitas MuhammadiyahCirebon (UMC) bersama perguruan tinggi muhammadiyah di Jawa Tengah, Jawa Barat, dan DKI Jakarta akan melaksanakan Program Kampus Merdeka untuk Desa Wisata dalam mencapai Sustainable Development Goals (SDGs). Kegiatan memberikan manfaat bagi para pelaku UMKM di Desa Kepuh dengan mendapatkan ketrampilan membuat akun media sosial, berlatih membuat postingan foto dengan angle yang menarik, serta caption yang mampu mengundang pembaca sehingga tertarik menelusuri lebih lanjut.Kata kata kunci: Branding; desa wisata; media sosial; UMKM.